Biological Infections Associated with Wearing Cosmetic Contact Lenses: Risks, Pathogens, and Preventative Measures: Mini Review Authors - Lina M. Shaker; Wan Nor Roslam Wan Isahak (AUIQ Complementary Biological System)
Cosmetic contact lenses are increasingly favored worldwide for their ability to enhance or alter aesthetic appearance. However, their use carries a higher risk of ocular infections, particularly when proper hygiene practices are neglected. This narrative review explores the biological and clinical aspects of infections associated with cosmetic lens usage, with a focus on pathogens such as Pseudomonas aeruginosa, Staphylococcus aureus (S. aureus), and Acanthamoeba. Key factors influencing infection susceptibility include microbial adhesion, biofilm formation, reduced oxygen permeability, and the effects of cosmetic pigments. The review further evaluates the role of lens material properties, including advancements in antimicrobial materials, in mitigating infection risks. In addition, it underscores the need for robust regulatory standards and widespread user education on hygiene practices to ensure safe lens use. By addressing these multifaceted aspects, this review aims to enhance understanding among users, healthcare professionals, and manufacturers, ultimately contributing to improved lens safety and ocular health outcomes.